Minocycline induced lupus with yellow colored chylous exudative pleural effusion. (2017) - Starobin, Daniel; Guller, Vladimir; Gurevich, Alexander; Tal, Sari
Abstract: Ninety years old male was admitted to hospital due to breathlessness. The prominent findings were extensive blue-grey skin pigmentation and large left chylothorax. Drug induced lupus was diagnosed due to either minocycline chronic treatment or no alternative illness to explain his sub-acute disease. Minocycline therapy was stopped with gradual improvement of pleural effusion and skin discoloration. This case is the first presentation of minocycline induced lupus with chylothorax.